HARNESSING SOCIAL MEDIA PLATFORMS AS INTEGRAL COMPONENTS OF BUSINESS MARKETING STRATEGIES IN THE DIGITAL AGE: A CASE STUDY WITHIN THE E-COMMERCE INDUSTRY - Muhamad Stiadi; Nur Qomariah; Dwi Apriyanti Kumalasari; Khusniyah; Riris Ambarwati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the dynamic landscape of contemporary business, the profound impact of social media in shaping marketing strategies is unequivocal. This case study delves into the strategic use of social media within the e-commerce industry, where online businesses have harnessed these platforms to engage with their customers, enhance brand visibility, and drive financial returns. Our study reveals compelling data, indicating that most e-commerce companies have successfully integrated social media into their marketing endeavors. The findings demonstrate substantial increases in customer engagement, brand recognition, and financial returns, underscoring the transformational potential of social media. These insights hold significant implications for business marketing in the digital age, emphasizing the strategic necessity of social media integration. We provide practical recommendations for e-commerce companies and businesses seeking to leverage social media effectively. Furthermore, this study identifies critical areas for future research, illuminating the evolving digital marketing landscape. In conclusion, the significance of social media as an integral component of contemporary marketing cannot be overstated, offering businesses a dynamic and indispensable tool for success.